Optimized delta expansion for relativistic nuclear models - Krein, G. [UNESP]; Marques de Carvalho, R. S.; Menezes, D. P.; Nielsen, M.; Pinto, M. B. (Springer, 1998)
The optimized delta-expansion is a nonperturbative approach for field theoretic models which combines the techniques of perturbation theory and the variational principle. This technique is discussed in the lambda phi(4) model and then implemented in the Walecka model for the equation of state of nuclear matter. The results obtained with the delta expansion are compared with those obtained with the traditional mean field, relativistic Hartree and Hartree-Fock approximations.